Exploring the Zone of Tolerance for Internal Customers in IT-Enabled Call Centers. (August 2013) - Hsieh, J. J. Po-An; Sharma, Piyush; Rai, Arun; Parasuraman, A.
Today, call center employees' service encounters with external customers are extensively supported with modern information technology (IT). However, prior research on service quality and zone of tolerance (ZOT) focuses primarily on external customers with little attention paid to how internal customers (e.g., service employees) respond to services provided by internal functions, particularly IT function that supports employees' IT use. Drawing on theory of administrative behavior and IT success literature, we conducted a study at a call center of a telecommunications firm and found that the impact of internal IT service quality (ITSQ) on employees' service quality (ESQ) to external customers, as well as on their satisfaction with and use of the deployed technology, exhibits a positive diminishing pattern as ITSQ increases from below to within and to above the ZOT. We also found that ITSQ's impact on ESQ employees' satisfaction with technology changes more dramatically around adequate service level than desired service level. Finally, we show that call center employees' satisfaction with technology partially mediates ITSQ's impact on ESQ. Besides adding to the service and IT literature, our findings suggest that managers should understand internal customers' different levels of expectations toward internal IT service and the differential performance impacts of those levels.